PREFERENCES OF CUSTOMERS AND IMPROVEMENT OF PRODUCTION AND SALES OF ORGANIC PRODUCTS IN SERBIA - Dašić, Goran; Radosavac, Adriana; Knežević, Desimir; Đervida, Ružica (Economics of Agriculture, 2019)
Promotion and sale of organic products require particular approach to introduce customers about the branding, packaging and advantages in comparison to conventional products. The aim of work is investigation which are sources of promotion of organic products use customers and effects of sources on trade improvement. In this study conducted interviews of 400 of customers through the mail. The results showed differences among customers according to: sources of their information about traits of products and market place, and their behavior and decision for use of organic product. Women more often use electronic media, professional literature, while man use magazine as a source of information. Both gender, male and female used internet equally. Customers old between 21 and 40 years more often bought in supermarkets and specialized stores, while customers of age between 41 and 60 years more often bought directly on market from producers. Customers who have more than 60 years buy on the market from producers and the supermarket. This differences depends of gender, age, education, as well as place of residence of customers